Pengaruh Leadership Style Terhadap Partisipasi Masyarakat dalam Pembangunan - Wahyuni, Desi; Teniro, Alwin (Universitas Gajah Putih, 2022)
Abstract: This study aims to determine whether reje's leadership style affects community participation in Pinangan village, Kebayakan District, Central Aceh Regency. The dependent variable (Y) used in this study is leadership style and the independent variable (X) is community participation. The sampling technique used is the Random Sampling technique. The data used is data collection techniques by disseminating questionnaires, observations, documentation studies. Hypothesis testing is carried out using Quantitative analysis and uses statistical testing with the Product Moment Correlation formula (Person Method). The calculation results for the hypothesis about the influence of Reje's leadership style on the participation of the village community showed a correlation of 0.60. Based on the results of the hypothesis test shows in correlation that leadership style has a significant effect on community participation, as shown that the Correlation Efficiency is worth 0.60 or 60%. and the sig value. 0.05 or 5%. variations or changes in community participation can be explained by the variables of leadership style. While the remaining 40% is explained by other factors that were not included in this research model. And the adjusted value of R² square shows the number 0.001 which means it is perfect.